Modeling the 2020 Novel Coronavirus Pandemic - Herz, Lori; Zurakowski, Ryan (McGraw-Hill's AccessEngineering., 2020)
Understanding how mathematical models can be used to predict and analyze the spread of infectious diseases is a topic of interest, especially in light of the COVID-19 pandemic. This case study provides an overview of epidemiological models, as well as an in-depth study of how to use the models and perform a goodness-of-fit analysis.